Injection of Recombinant Tissue Plasminogen Activator into Extracorporeal Membrane Oxygenators Postpones Oxygenator Exchange in COVID-19. Issue 8 (16th May 2022) - Mang, Sebastian; Danziger, Guy; Metz, Carlos; Rixecker, Torben; Becker, André; Omlor, Albert J.; Jentgen, Christophe; Schmoll, Christian; Seiler, Frederik; Reyher, Christian; Muellenbach, Ralf M.; Bals, Robert; et al.
Abstract : Coronavirus disease 2019 (COVID-19) has drastically increased the number of patients requiring extracorporeal life support. We investigate the efficacy and safety of low-dose recombinant tissue-type plasminogen activator (rtPA) injection into exhausted oxygenators to delay exchange in critically ill COVID-19 patients on veno-venous extracorporeal membrane oxygenation (V-V ECMO). Small doses of rtPA were injected directly into the draining section of a V-V ECMO circuit. We compared transmembrane pressure gradient, pump head efficiency, membrane arterial partial oxygen pressure, and membrane arterial partial carbon dioxide pressure before and after the procedure. Bleeding was compared with a matched control group of 20 COVID-19 patients on V-V ECMO receiving standard anticoagulation. Four patients received 16 oxygenator instillations with rtPA at 5, 10, or 20 mg per dose. Administration of rtPA significantly reduced transmembrane pressure gradient (Δ p m = 54.8 ± 18.1 mmHg before vs . 38.3 ± 13.3 mmHg after, p < 0.001) in a dose-dependent manner (Pearson's R −0.63, p = 0.023), allowing to delay oxygenator exchange, thus reducing the overall number of consumed oxygenators. rtPA increased blood flow efficiency η (1.20 ± 0.28 ml/revolution before vs . 1.24 ± 0.27 ml/r, p = 0.002). Lysis did not affect membrane blood gases or systemic coagulation. Minor bleeding occurred in 2 of 4 patients (50%) receiving oxygenator lysis as well as 19 of 20 control patients (95%). Lysis of ECMO oxygenators effectively delays oxygenator exchange, if exchange is indicated by an increase in transmembrane pressure gradient. Application of lysis did not result in higher bleeding incidences compared with anticoagulated patients on V-V ECMO for COVID-19.